Matrix Inverse Sum Calculation
Given the matrix:
A = | 1 2 2 | | 3 2 3 | | 1 1 2 |
The inverse matrix is represented as:
A-1 = | a11 a12 a13 | | a21 a22 a23 | | a31 a32 a33 |
The sum of all elements in A-1 is:
Step 1: Interpret the sum of elements of \(A^{-1}\). Define \(A^{-1} = [a_{ij}]\). The sum of all entries in \(A^{-1}\) is
\[\sum_{i=1}^{3}\,\sum_{j=1}^{3} a_{ij}.\] One efficient way to find this is to observe that
\[\sum_{i,j} a_{ij} \;=\; \mathbf{1}^T\,A^{-1}\,\mathbf{1},\]
where \(\mathbf{1} = (1,\,1,\,1)^T\).
Step 2: Solve \(A\,x = \mathbf{1}\) to locate row-sums of \(A^{-1}\). If \(x = A^{-1}\mathbf{1}\), then each component of \(x\) is precisely the sum of one row of \(A^{-1}\). Hence
\[ A\,x \;=\; \mathbf{1}. \] Let \(x = (x_1,\,x_2,\,x_3)^T\). Then:
\[\begin{pmatrix} 1 & 2 & 2 \\ 3 & 2 & 3 \\ 1 & 1 & 2 \end{pmatrix} \begin{pmatrix} x_1 \\ x_2 \\ x_3 \end{pmatrix} = \begin{pmatrix} 1 \\ 1 \\ 1 \end{pmatrix}.\]
Step 3: Solve for \((x_1,\,x_2,\,x_3)\).
Subtracting the first equation from the third gives \(x_2 = 0\).
From the second minus thrice the first: \(4x_2 + 3x_3 = 2\). With \(x_2=0\), we get \(3x_3 = 2\implies x_3 = \tfrac{2}{3}\).
Back-substituting into the first:
\(x_1 + 2\cdot 0 + 2\cdot \tfrac{2}{3} = 1 \implies x_1 + \tfrac{4}{3} = 1 \implies x_1 = -\tfrac{1}{3}.\)
Thus \[ x = (x_1,\,x_2,\,x_3) = \Bigl(-\tfrac{1}{3},\,0,\,\tfrac{2}{3}\Bigr). \]
Step 4: Sum of all elements of \(A^{-1}\).
That sum is \[ \mathbf{1}^T(A^{-1}\mathbf{1}) = \mathbf{1}^T\,x = x_1 + x_2 + x_3 = -\tfrac{1}{3} + 0 + \tfrac{2}{3} = \tfrac{1}{3}. \] Hence \(\boxed{\tfrac{1}{3}}\) is the value of \(\sum_{i,j} a_{ij}\).
Calculate the determinant of the matrix:
A, B, C, D are square matrices such that A + B is symmetric, A - B is skew-symmetric, and D is the transpose of C.
If
\[ A = \begin{bmatrix} -1 & 2 & 3 \\ 4 & 3 & -2 \\ 3 & -4 & 5 \end{bmatrix} \]
and
\[ C = \begin{bmatrix} 0 & 1 & -2 \\ 2 & -1 & 0 \\ 0 & 2 & 1 \end{bmatrix} \]
then the matrix \( B + D \) is: